Caracterización del microcrédito en las instituciones financieras de la provincia de Zamora Chinchipe - Jima Vaca, Fahina Bernarda (2024)
Microcredit is a form of financing that involves the provision of certain sums of money to low-income people, generally excluded from access to traditional financial services, so that they can start, expand or improve small, self-employed businesses. This practice originated as part of the microfinance initiative, whose main objective is to alleviate poverty and promote financial inclusion. In this context, the general objective of this research was to characterize microcredit in financial institutions in the province of Zamora Chinchipe and to reveal the impact on the sector. Structured interviews with 14 questions related to microcredit were conducted with 15 local financial institutions. In addition, information obtained from official websites was used to analyze the relationship between the variables of microcredit, poverty and unemployment. This research made it possible to identify specific characteristics in the elements of credit, such as amounts, terms, guarantees and interest rates, among other aspects. It was also possible to establish a comparative level among institutions to determine those with the best practices in the granting of microcredits. Among the main findings of the research are that the cooperative COOPERCO is the one that offers the best opportunities for access to the microenterprise sector because it is the most inclusive with people who have a low credit history, in addition, its interest rates are the lowest. Meanwhile, the public bank represented by BanEcuador is the sector that has made more placements in the microcredit portfolio until 2021. Finally, it was determined that the relationship between microcredit and the level of poverty and unemployment is not significant.